Four 3D Cd(II)-based metal organic hybrids with different N,N `-donor spacers: syntheses, characterizations, and selective gas adsorption properties - Bhattacharya, Biswajit; Dey, Rajdip; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (Crystal Growth & Design, 2013)
{Four new metal organic frameworks with bivalent cadmium, disodium succinate (Na(2)suc), and four different N,N'-donor ligands, i.e., {[Cd(L1)(suc)]center dot(H2O)(3)}(n) (1), {[Cd(L2)(suc)]center dot(H2O)(2)\

Flexible dicarboxylate based pillar-layer metal organic frameworks: differences in structure and porosity by tuning the pyridyl based N, N ` linkers - Dey, Rajdip; Bhattacharya, Biswajit; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (CrystEngComm, 2014)
{Dicarboxylate supported metal organic hybrids of Co(II), Zn(II) and Cd(II) have been synthesized using two different pyridyl based N, N' linkers having Schiff base functionalized site. The use of flexible dicarboxylate glutarate in designing such frameworks has created a marked diversity in topology. The different N, N' donor linkers also played an active part in the channel modification in the synthesized MOFs. The structural and topological diversity has been analyzed from the single crystal X-ray structure. Five compounds, {[Co(azpy)(glut)]center dot(CH3OH)}(n) (1), {[Co(meazpy)(glut)(H2O)(2)]center dot (H2O)(3)